Educação da mulher e evangelização católica: um olhar sobre a Escola Normal N. Sra. do Patrocínio - Silva, Michelle Pereira da (2005)
The present study attempts to understand women in the context of Modernism, reading the classics of the Modernist Education and perceiving how the formation of women was linked to her role as mother-wife. In the same manner, we configured this reality within the Brazilian context, learning how the Roman Catholic Church utilized education, more precisely, the education of women, as an important means of the re-Christianization, in an era when the conflicts between Church and State were amalgamated, also, by an educational action. We focused on the participation of the Congregations that arrived in Brazil at the end of the XIX century, specifically to the region the of Triângulo Mineiro/Alto Paranaíba, so as to understand the context by which the Escola Normal N. Sra. do Patrocínio (Normal School Our Lady of Patrocínio) was constituted, becoming an important educational center for the formation of normal school students in the region. Upon these points we focus on education as an important vehicle for the Catholic evangelization. To develop our analyses, this study anchored itself initially on bibliographical and documental , attempting to learn this process of the development of female education during Modernism, and specifically, in the Brazilian context at a national and regional level (Patrocínio, MG). In search of this knowledge, we searched to better concept of the day-to-day life of the Normal School (Escola Normal). We formulated interviews with former students of the Normal School, which came to be of great value, not only for our research, but also for a better comprehension of the values and choices that were transmitted, appropriated or not by the lives of the students. Through the interpretations made, we understood that the education of females, were related to the social role that was expected of women: mother, wife, and house-wife. When we think of religious education, its formation was strickly associated to a process of evangelization of the actual society: molding the woman into an evangelizer. Such results allowed us to understand that her professionalization in the teaching profession was associated to the desired standards expected of a woman of good conduct: mother wife teacher, so as, to act in the different social setting, be it to heed the primary course demands, or the evangelization as catechizer.